PEMBERIAN BANTUAN TRANSPORTASI BAGI SISWA DI KAWASAN HINTERLAND KOTA BATAM (STUDI KASUS PULAU SARANG) - Dhea Ananda Putri Putri; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sarang Island is an island in the Hinterland region of Batam City.  The phenomenon that arises in education on the Sarang Island is the government budget for boat fuel money to take children to school less, the mindset of parents of students lacking on the importance of children's education, low economy, and the ability of teachers not yet qualified.  The purpose of this study was to determine the development of education on the island of the city of Batam.  The concept that can be used in this study is that there are three factors that can influence the success of implementation according to Ripley and Franklin, namely Compliance, Routine Activity, and Policy Performance.  The selection of informants in this study used a purposive sampling technique.  The results showed that the Batam City Education Office had not been maximized in the development of education in the Hinterland region especially the Sarang Island.  Inhibited mindset of parents in education so that school teachers try to change the mindset of parents towards their children's education.  The inhibiting factors of the development of the education sector on the island of the Sarang is the profession of parents is a fisherman and a low economy and information that is difficult to enter into the island environment. Keywords: Policy, Policy implementation, Development of education